Industrial/Breadwinner Masculinities and Climate Change: Understanding the ‘White Male Effect’ of Climate Change Denial - Pulé, Paul; Hultman, Martin (Climate Hazards, Disasters, and Gender Ramifications, 2019)
Modern Western men and masculinities are shaped by socialised performances that are conditioned rather than predetermined. This chapter considers the lives of those men who occupy the most privileged positions in society in the Global North and the masculine socialisations that define them. The correlations despite class disparities are blaringly evident; they share in common an addictive allegiance to the hegemonic allegiances of hyper-masculinities or the hierarchicalisation of wealth distribution generated by natural resource exploitation. The chapter focuses on a critical analysis of industrial/breadwinner masculinities, reflective of the typology’s most acute intersections with white male effect and its compounding impacts of climate change denial. In the modern context, the beneficiaries of extractive dependent industrialisation are not only the owners of the means of production, but also include fossil fuel and mining executives, financial managers and bankers, corporate middle and senior level managers and administrators–the vast majority of direct beneficiaries being Western, white and male.